The Impact of a Minimum Wage Change on the Distribution of Wages and Household Income - Paul Redmond; Karina Doorley; Seamus McGuinness (Institute of Labor Economics (IZA), 2020)
We use distributional regression analysis to study the impact of a six percent increase in the Irish minimum wage on the distribution of hourly wages and household income. Wage inequality, measured by the ratio of wages in the 90th and 10th percentiles and the 75th and 25th percentiles, decreased by approximately eight percent and four percent respectively. For young workers, aged under 25, the effects were far greater, with a 24 percent reduction in the ratio of wages in the 90th and 10th percentiles. The results point towards wage spillover effects up to the 30th percentile of the wage distribution. We show that minimum wage workers are spread throughout the household income distribution and are often located in high-income households. Therefore, while we observe strong effects on the wage distribution, the impact of a minimum wage increase on the household income distribution is quite limited.
Keywords: J31; J38; K31; 330; minimum wage; inequality; wage spillovers; distributional regression